2012
DOI: 10.1007/s13197-012-0876-8
|View full text |Cite
|
Sign up to set email alerts
|

Microwave blanching and drying characteristics of Centella asiatica (L.) urban leaves using tray and heat pump-assisted dehumidified drying

Abstract: The appropriate stage of maturity of Centella asiatica (L.) Urban leaves was investigated. Mature leaves with large diameter contained high total phenolics and % inhibition. Microwave blanching for 30 s retained the highest total phenolics and the microwave blanching for 30 s and 45 s retained the highest % inhibition. Modified Henderson and Modified Chung-Pfost models showed the best fit to both fresh and blanched leaves for equilibrium moisture content, X e 0 f(RH e , T) and equilibrium relative humidity, RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…It was observed from the response surface plots (Figures d and d) that increase in microwave blanching time caused a reduction in total color change due to the complete inactivation of enzymes which causes color changes in samples. The microwave blanching inhibited enzymatic browning reaction and helped to improve the green color of dried C. asiatica leaves (Trirattanapikul & Phoungchandang, ). Soysal and Soylemez () studied water and microwave blanching of carrot slices and reported that microwave blanching was more effective for inactivation of enzymes and retention of vitamin C. Increasing the brine solution to sample ratio from 0 to 2 decreased the total color change.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed from the response surface plots (Figures d and d) that increase in microwave blanching time caused a reduction in total color change due to the complete inactivation of enzymes which causes color changes in samples. The microwave blanching inhibited enzymatic browning reaction and helped to improve the green color of dried C. asiatica leaves (Trirattanapikul & Phoungchandang, ). Soysal and Soylemez () studied water and microwave blanching of carrot slices and reported that microwave blanching was more effective for inactivation of enzymes and retention of vitamin C. Increasing the brine solution to sample ratio from 0 to 2 decreased the total color change.…”
Section: Resultsmentioning
confidence: 99%
“…For both the X e = f (RH, T ) and RH e = f ( X , T ) functions, the Modified Halsey model has the best fit for fresh A. paniculata leaves while the Modified Henderson model showed a better fit for blanched A. paniculata leaves based on the highest R 2 and the lowest SEE and RMSE. The Modified Halsey model generally has the best fit for medicinal and aromatic plants (Soysal & Oztekin, ) while the Modified Henderson model has the best fit for plants with high fiber content (Phoungchandang et al, ; Trirattanapikul & Phoungchandang, ). In this work A. paniculata leaves had a rather high fiber content of 9.51% d.b.…”
Section: Resultsmentioning
confidence: 99%
“…The blanched A. paniculata leaves were found to have a shorter drying time compared to the unblanched samples by 33.33% in HPD at 60 °C. Trirattanapikul and Phoungchandang () reported that the microwave blanching followed by HPD could reduce the drying time by 31.2%. The Arrhenius model described the temperature of K in all cases, with R 2 > .93.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations